Transformasi digital dan risiko operasional: Tantangan serta strategi mitigasi pada perbankan syariah - Ningrum, Ajeng Rizqi (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze operational risk challenges arising from digital transformation in Islamic banking and examine mitigation strategies that can be implemented to maintain operational stability and banking system resilience. This analysis was conducted to provide a comprehensive overview of the changing spectrum of operational risk, from traditional risks based on human error to technology-based risks such as system failure, cybersecurity threats, digital service disruptions, and potential fraud within the digital banking ecosystem. This study employs a descriptive qualitative approach through a literature review by utilizing relevant literature, regulations, and previous studies related to operational risk management and Islamic banking digitalization. The results indicate that digital transformation, while improving efficiency, service speed, and product innovation, also creates higher operational risk complexity due to dependence on technological infrastructure, information system integration, and uneven human resource readiness. The findings also show that effective mitigation strategies require strengthening internal controls, implementing technology-based risk management, reinforcing cybersecurity frameworks, adopting business continuity plans, and establishing integrated information technology governance. These findings contribute significantly to strengthening the operational risk mitigation framework in Islamic banking and provide an evaluation basis for regulators, practitioners, and academics in supporting operational resilience in the era of digital transformation.